Comparison of eccentric utilization ratio of elite karate (kata) with elite Wushu athletes - Cheah, B. C.; Loh, T. C.; Tan, C. H. E.; Beaven, C. M. (Revista de Artes Marciales Asiaticas, 2016)
The results of this study suggest that there was no significant difference in EUR between the genders or Karate (Kata) and Wushu Taolu athletes. In support of our findings, previous authors have not observed any specific gender differences on the EUR (McGuigan, et al., 2006). It was however apparent that the Karate athletes showed an EUR value of below the value of 1.00 which was generally lower than was observed in the Wushu athletes. This difference may be due to the nature of the Karate Kata event where exponents are required to execute techniques from a lowered stance the majority of the time. As for the Wushu event, there are more jumps in a Taolu when compared to Karate Kata and more dynamic athletic movements. Higher EUR values are indicative of a greater reliance on the stretch shortening cycle (McGuigan, et al., 2006). Different training practices may also account for the differences observed as a lesser degree of augmentation (EUR) in long distance runners has been observed when compared to strength matched controls and this augmentation was correlated to the compliance of the muscle tendon unit in the knee extensor muscles (Kubo, et al., 2000). Further, compliance of the vastus lateralis muscle has also been demonstrated to be negatively correlated to 100 m sprint time (Kubo, et al., 2000b). One limitation of the present study is that comparison of EUR at different phase of training was not taken into account as an earlier study has shown that there can be a significant difference between off-season and preseason EUR values (McGuigan, et al., 2006).